Managing Pain Related Gout Arthritis in Elderly: An Intervention Using Ergonomic Exercise and Warm Lemongrass Compress in Joyotakan Village, Surakarta - Fernanda Ayu Dentaningtyas; Didik Iman Margatot; Nur Haryani (Al-Hijrah Indonesia, 2025)
Background: Gouty arthritis is a degenerative joint disease that affects many elderly people, characterized by severe pain that can interfere with daily activities. Non-pharmacological treatments are an essential alternative in reducing this pain. Objective: To determine the effectiveness of ergonomic exercises and warm compresses of lemongrass on pain levels in elderly people with gouty arthritis in RT 03 RW 02 Joyotakan Village, Serengan District, Surakarta City. Method: The research method employs a descriptive approach with observation sheets monitored by two respondents. Results: The study showed a decrease in pain levels in both respondents, from moderate to mild pain, and this improvement persisted after the intervention. Pain reduction was achieved through increased muscle relaxation and improved blood circulation, resulting from a combination of gymnastic movements and the analgesic effect of lemongrass leaves. Conclusion: Ergonomic gymnastics and warm compresses made from lemongrass leaves are effective in reducing pain levels in the elderly with gouty arthritis and can be applied as an alternative non-pharmacological therapy in the community.